Local bond stress–slip relationship of ribbed reinforcing bars embedded in UHPC: Experiment, modeling, and verification. (1st June 2023) - Xu, Tengfei; Bian, Xianggang; Liu, ZhiFeng; Yang, Jingning; Zhang, Ziyang
Abstract: This paper provides an experimental and analytical investigation on the bond behavior of reinforcing bars embedded in ultra-high performance concrete (UHPC) via a series of pullout tests. The local bond stress–slip relationship and global bond slip behavior were tested using specimens with embedment lengths of 2 d, 5 d, and 7 d, where d is the diameter of the reinforcing bar. Four curing procedures and two loading ages for the UHPC were adopted to achieve different compressive strengths with the same mixture. During the test, the tension force and slip at the free end of the reinforcing bar were measured. The strain distribution along the anchorage length was measured using a distributed optical fiber sensor glued to an internal groove on the bar. The experimental results show that the ascending part of the local bond stress–slip relationship is nearly linear. A simplified local bond stress–slip model is proposed and verified using the tested strain distribution and the slip of the reinforcing bar in long specimens. This model is used to discuss the distribution form of the slip and bond stress along the anchorage length and the theoretical development length for pullout failure. The concrete surrounded reinforcing bar was subjected to the tension–compression–compression triaxial stress state, determining the higher bond strength of the UHPC compared with conventional concrete. When the anchorage length is no longer than two times the diameter of the bar, the slip and bond stress can be assumed to have a uniform distribution, whereas when the anchorage length is less than 7.5 times the diameter of the bar, the slip and bond stress can be assumed to have a linear distribution. Highlights: A simplified local bond stress–slip model for UHPC is proposed and verified. The lower tensile stress-to-strength ratio of UHPC surrounding a bar determines its high bond strength. When l d ≤ 7 . 5 d, the slip and bond stress can be assumed to have a linear distribution.